Routledge international handbook of green criminology - South, Nigel; Brisman, Avi (Routledge international handbooks, 2013)
Introduction: Horizons, Issues and Relationships in Green Criminology / Avi Brisman and Nigel South. -- Part I: History, Theory and Methods. A Guide to a Green Criminology / Nigel South, Avi Brisman, and Piers Beirne ; Reflections on Green Criminology and its Boundaries: Comparing Environmental and Criminal Victimization and Considering Crime from an Eco-city Perspective / Michael J. Lynch ; The Ordinary Acts that Contribute to Ecocide: A Criminological Analysis / Robert Agnew ; The Contemporary Horizon of Green Criminology / Lorenzo Natali ; Innovative Approaches to Researching Environmental Crime / Diane Heckenberg and Rob White. -- Part II: International and Transnational Issues for a Green Criminology. Conservation Criminology and the "General Accident" of Climate Change / Mark Halsey ; The Criminogenic Consequences of Climate Change: Blurring the Boundaries between Offenders and Victims / Matthew Hall and Stephen Farrall ; Air Crimes and Atmospheric Justice / Reece Walters ; Crude Laws: Treadmill of Production and State Variations in Civil and Criminal Liability for Oil Discharges in Navigable Waters / Matthew B. Greife and Paul B. Stretesky ; Food Crime: A Green Criminology Perspective / Hazel Croall ; Nature for Rehabilitating Offenders and Facilitating Therapeutic Outcomes for Youth at Risk / Jules Pretty, Carly Wood, Rachel Hine and Jo Barton. -- Part III: Region-Specific Problems: Some Case Studies. The Amazon Rainforest: A Green Criminological Perspective / Tim Boekhout van Solinge and Karlijn Kuijpers ; The Control of Conflict Minerals in Africa and a Preliminary Assessment of the Dodd-Frank Wall Street Reform and Consumer Act / Richard D. Clark ; Green Issues in South-Eastern Europe / Katja Eman and Gorazd Meško. -- Part IV: Relationships in Green Criminology: Environment and Economy. Eco-Global Criminology and the Political Economy of Environmental Harm / Rob White ; The Environment and the Crimes of the Economy / Vincenzo Ruggiero ; Evading Responsibility for Green Harm: State-Corporate Exploitation of Race, Class, and Gender Inequality / Emily Gaarder ; Public Perceptions of Corporate Environmental Crime: Assessing the Impact of Economic Insecurity on Willingness to Impose Punishment for Pollution / Tara O'Connor Shelley and Michael J. Hogan. -- Part V: Relationships in Green Criminology: Humans and Non-Human Species ; Uncovering the Significance of and Motivation for Wildlife Trafficking / Tanya Wyatt ; Victimisation of Women, Children and Non-Human Species Through Trafficking and Trade: Crimes Understood Through an Ecofeminist Perspective / Ragnhild Sollund ; Environmental Justice, Animal Rights, and Total Liberation: From Conflict and Distance to Points of Common Focus / David N. Pellow. -- Part VI: Relationships in Green Criminology: Environment and Culture. Tangled Up in Green: Cultural Criminology and Green Criminology / Jeff Ferrell ; "This is the North, Where We Do What We Want:" Popular Green Criminology and "Little Red Riding Hood" Films / Steven Kohm and Pauline Greenhill ; Coastline Conflict: Implementing Environmental Law in Salvador da Bahia, Brazil / Stephanie Kane ; Matter All Over the Place: Litter, Criminology and Criminal Justice / Nic Groombridge ; Conclusion: The Planned Obsolescence of Planet Earth? How Green Criminology Can Help Us Learn From Experience and Contribute to Our Future / Avi Brisman and Nigel South.